DOCUMENTARY TERMS IN RUSSIAN LITERATURE (TAMADDUN NURI JURNALI, 2024)
At the beginning of the XX century, a new literature of a stable, universally recognized name was born, for which there is still no place in science: almost everyone calls it in their own way and privately tries to determine its place in the traditional series – “literature of fact”, “nonfiction”, etc.